PENERAPAN PROJECT BASED LEARNING (PjBL) KAOS TIE DYE DENGAN SHIBORI “NATURAL DYE” UNTUK MENUMBUHKAN SIKAP KERJASAMA PADA SISWA KELAS 4 SEKOLAH DASAR - Atun Hasanah, Imra; Wibawa, Sutrisna; Susanto, Moh. Rusnoto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to analyze the application of project based learning (PjBL) in SBdP and Civics learning to foster an attitude of cooperation in grade 4 students at Parakan Muhammadiyah Elementary School. This research method uses qualitative methods. The subjects of this research were 23 grade 4 students at SD Muhammadiyah Parakan. Of the 23 students, all of them succeeded in making this learning work together by making Tie Dye t-shirts with